Auditory Contagious Yawning in Humans: An Investigation into Affiliation and Status Effects - Massen, Jorg J. M.; Church, Allyson M.; Gallup, Andrew C. (Frontiers in Psychology, 2015)
While comparative research on contagious yawning has grown substantially in the past few years, both the interpersonal factors influencing this response and the sensory modalities involved in its activation in humans remain relatively unknown. Extending upon previous studies showing various in-group and status effects in non-human great apes, we performed an initial study to investigate how the political affiliation (Democrat versus Republican) and status (high versus low) of target stimuli influences auditory contagious yawning, as well as the urge to yawn, in humans. Self-report responses and a subset of video recordings were analyzed from 118 undergraduate students in the US following exposure to either breathing (control) or yawning (experimental) vocalizations paired with images of former US Presidents (high status) and their respective Cabinet Secretaries of Commerce (low status). The overall results validate the use of auditory stimuli to prompt yawn contagion, with greater response in the experimental than the control condition. There was also a negative effect of political status on self-reported yawning and the self-reported urge to yawn irrespective of the condition. In contrast, we found no evidence for a political affiliation bias in this response. These preliminary findings are discussed in terms of the existing comparative evidence, though we highlight limitations in the current investigation and we provide suggestions for future research in this area.